Antibacterial activity of acmella paniculata extracts against streptococcus mutans - Salehuddin N.S.B.; Ghafar S.A.A.; Rohazila Mohamad Hanafiah (J. K. Welfare and Pharmascope Foundation, 2024)
Indexed by Scopus